Penerapan Permainan Interaksi Edukasi pada Pendidikan Taman Kanak-Kanak - Syarboini Syarboini (Multiverse: Open Multidisciplinary Journal, 2025)
The implementation of interactive educational games has become an important pedagogical strategy in early childhood education, particularly in cultivating Islamic values among preschool children. This study examines the application of interactive educational games at Miftahul Jannah Kindergarten as a medium of educational interaction between teachers and learners. The research addresses how play-based learning activities function as an interactive educational system that supports cognitive, affective, and moral development in early childhood. Using a qualitative descriptive approach, data were collected through classroom observations, documentation, and analysis of teaching and learning practices. The findings reveal that interactive educational games effectively integrate key components of educational interaction, including learning objectives, instructional activities, teaching materials, learning resources, instructional tools, teaching methods, and evaluation. These components work synergistically to facilitate meaningful interaction that goes beyond the transmission of academic content and contributes to the development of children’s knowledge, skills, attitudes, and Islamic values. The study argues that interactive educational games serve not only as instructional tools but also as transformative media that support holistic child development through enjoyable, value-oriented, and contextually meaningful learning experiences in kindergarten education.